Assessing the factor structure of the Spreitzer’s Psychological Empowerment Scale among Malaysian teachers - Ahmad Zamri Khairani; Aziah Ismail; Norliza Abdul Kadir (Jurnal Cakrawala Pendidikan, 2021)
Psychological empowerment is one of the compelling factors that drive employees to be more initiative and innovative and Spreitzer's Psychological Empowerment Scale (PES) has been widely used to measure it. Nevertheless, PES stability has not been determined in the Malaysian context, limiting its meaning and interpretation. Hence, this study examines the factor structure of the scale among Malaysian teachers. The scale structure was investigated using confirmatory factor analysis (CFA) simultaneously with the convergent validity, discriminant validity, and reliability assessment. CFA results of factor loadings and average variance extracted revealed significant evidence of convergent validity while the Fornell-Larcker procedure produced an outcome that supported high discriminant validity of the PES. The reasonable values of the goodness-of-fit indices show that overall, the data fit well. Also, based on the values of the composite reliability and Cronbach’s alpha, measurement using the scale demonstrated high internal consistency. Thus, the findings confirmed the stability of the factor structure and therefore provided evidence of generalizability of the scale into the Malaysian context.